Evaluation of mechanical and thermal properties after chemical degradation of PVC and HDPE geomembranes - Lodi, Paulo César [UNESP]; de Souza Bueno, Benedito; Hamada, Jorge [UNESP]; de Oliveira, Eduardo Luis [UNESP]; da Silva, Gustavo Henrique Ribeiro [UNESP] (My University, 2013)
Chemical compatibility between geomembranes and site-specific waste liquids should be assessed since the waste liquids are highly complex mixtures. This paper presents some considerations about the chemical compatibility of geomembranes and some results of mechanical tests in HDPE and PVC geomembranes that were exposed to leachate and chemical residue (niobium). PVC and HDPE geomembranes of two thicknesses were tested: 1.0, 2.0 mm (PVC) and 0.8, 2.5 mm (HDPE). The results obtained show that after exposure the PVC geomembranes (1.0, 2.0 mm) were more rigid and stiffer than fresh samples. The HDPE geomembranes, on the other hand, when exposed to leachate and niobium residue presented increases in deformation. Melt flow index (MFI) tests were also carried out to verify the oxidation. © 2013 ejge.
Keywords: Chemical degradation; Mechanical; PVC and HDPE geomembranes; Thermal tests; Chemical compatibility; Chemical residues; Mechanical and thermal properties; Mechanical tests; Melt flow index; Degradation; Niobium; Geomembranes; degradation; geomembrane; mechanical property; thermodynamic property